Adult female with symptomatic AVPR2-related nephrogenic syndrome of inappropriate antidiuresis (NSIAD). (9th February 2018) - Hague, Jennifer; Casey, Ruth; Bruty, Jonathan; Legerton, Tom; Abbs, Stephen; Oddy, Susan; Powlson, Andrew S; Majeed, Mohamed; Gurnell, Mark; Park, Soo-Mi; Simpson, Helen
Summary: Activating mutations in AVPR2 are associated with nephrogenic syndrome of inappropriate antidiuresis (NSIAD). NSIAD causes hyponatremia, decreased serum osmolality and clinical symptoms, which may present from birth or in infancy and include hypotonia, irritability, vomiting and/or seizures. Symptoms in later life are often less specific and include malaise, dizziness, confusion, tiredness and headache. NSIAD is a rare X-linked condition, which is associated with a variable phenotype in males, of whom some present in infancy but others do not become symptomatic until adulthood, or occasionally, never. Female carriers may present with episodes of hyponatremia, usually found incidentally. Literature in this field is limited; namely, two clinical reports describing a female proband, both diagnosed in infancy. We describe, for the first time, the case of an adult female proband with NSIAD, who had longstanding associated symptoms of tiredness, headache, temporary memory loss and mood changes as well as hyponatremia and decreased serum osmolality. A water load test demonstrated an inability to dilute urine and gene sequencing confirmed a recurrent activating mutation in AVPR2 . The variant was inherited from the proband's mother who had had longstanding episodes of transient asymptomatic hyponatremia. This is the third report of a female proband with NSIAD and is the first female reported who sought medical treatment for chronic symptoms from adulthood. This case acts as a reminder of the importance of considering NSIAD as a diagnosis in females of all ages with unexplained hyponatremia. Learning points: Activating mutations in the AVPR2 gene are associated with the rare X-linked condition nephrogenic syndrome of inappropriate antidiuresis. NSIAD is associated with hyponatremia, decreased serum osmolality and inappropriately increased urinary osmolality. Early clinical symptoms in infancy include hypotonia, irritability, vomiting and/or seizures. Symptoms in later life include malaise, dizziness, confusion, tiredness and headache. NSIAD should be considered in female, as well as male, patients who present with unexplained hyponatremia and decreased serum osmolality. Family history may reveal relevant symptoms or biochemical features in other family members. However, family history may not always be informative due to the variable nature of the condition or if the proband has a de novo pathogenic variant. A water load test with measurement of AVP may be informative in distinguishing NSIAD from SIADH. Measurement of co-peptin levels may be considered, in substitution for direct measurement of AVP. Patients with NSIAD should be counseled about appropriate daily fluid volume intake. Potential episodes of fluid overload should be avoided.